Motivation and Work Environment in the era of flexibility: Optimizing Employee Engagement for Maximum Performance at PT. Mandiri Andalan Utama - Dhiva Muhamad Fauzan Sabani; Nuraeni Nuraeni (Dinasti Publisher, 2025)
Creating a work environment that supports productivity while maintaining employee engagement. Companies need highly motivated human resources to provide good performance to achieve maximum work performance. Good performance can be created from an effective and efficient work environment. This study aims to determine Motivation and Work Environment in the Era of Flexibility in Optimizing Employee Engagement for Maximum Performance at PT Mandiri Andalan Utama located at Jl. Sultan Iskandar Muda No. 30 A-B Arteri Pondok Indah Kebayoran Lama, South Jakarta 12240. The data collection methods used in this research are observation, interview and questionnaire. The population was 40 employees, and the number of samples used in this study were 40 respondents, using the non-probability sampling method with saturated sample technique. The data analysis methods used in this study are measurement models (outer models), structural models (inner models) and SmartPLS criteria. Based on the results of the study Motivation has an insignificant effect on Employee Engagament, Work Environment has a significant positive effect on Employee Engagement, Motivation has an insignificant effect on Performance, Work Environment has an insignificant effect on performance, Employee Engagement has no effect on mediating the relationship between motivation and performance, Employee Engagement has no effect on mediating the relationship between Work Environment and performance.